Concerns of Balochistan: Effects and Implications on Federation of Pakistan - Umbreen Javaid (Journal of Political Studies, 2010)
One of the most serious threats to the federation of Pakistan is the rising insurgency in Balochistan. Although, geographically this is the largest province, demographically it is the smallest and the most under-developed federating unit. An overview of under-development in Balochistan reveals the alarming situation which needs to be tackled by the government on top priority basis. Over the years, the deprivation amongst Balochis has caused a number of uprisings against the federal government. Resultantly, time to time various governments have carried out military operations to curtail these insurgent movements. Unfortunately, being kept away from the mainstream politics of Pakistan, the Balochis have a number of serious grievances, which over the time have developed into nationalistic feelings posing threats to the federation of Pakistan. The growing resentment among the local population calls for greater control over its own resources, more autonomy, role in mega projects, issues of outside settlers, missing persons and extremism. This paper is an attempt to analyze these issues. It also suggests some measures for improvement.